2003
DOI: 10.14429/dsj.53.2261
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of telemetry stations based on site selection (Short Communication)

Abstract: In a test range, selection of sites for deployment of mobile telemetry stations plays a crucial role for acquiring and tracking any airborne vehicle under test. Efforts have been made to correlate the tracking nerformance of the auto track stations based on site selection for various test flights conducted from dzerent launching pads. Some of the tracking methodologies discussed in this piper are singlechannel amplitude comparison monopulse (SCACMP) technique and E-SCAN technique. Also, the performance of a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Lastly, the electronically scanned feed combines the best features of the previous two methods to generate tracking errors (RCC, 2008). It has been found that electronically scanned feed subsystems have a superior auto-tracking performance overall (Goswami, Sucharita, & Arya, 2003). For the purposes of this paper, we will focus on the electronically scanned feed assembly because the TTS antennas being analyzed for this paper utilize this type of feed assembly system.…”
Section: B Auto-tracking Systemsmentioning
confidence: 99%
“…Lastly, the electronically scanned feed combines the best features of the previous two methods to generate tracking errors (RCC, 2008). It has been found that electronically scanned feed subsystems have a superior auto-tracking performance overall (Goswami, Sucharita, & Arya, 2003). For the purposes of this paper, we will focus on the electronically scanned feed assembly because the TTS antennas being analyzed for this paper utilize this type of feed assembly system.…”
Section: B Auto-tracking Systemsmentioning
confidence: 99%
“…The location of ground receiving station in space diversity is estimated using predicted trajectory and G/T of respective ground receiving station. These ground stations are connected in network and operated in different modes such as Mono-pulse Mode (amplitude comparison mode), E-Scan Mode 6 and Internal Designated Mode (IDM-Simulated and predicted information) to track the vehicle.…”
Section: Introductionmentioning
confidence: 99%
“…In test ranges throughout the world, multiple auto-tracking sensors like electro-optical tracking stations (EOTS) and tracking radars are deployed at various geographical locations for generation of the trajectory of the missile under test (MUT). Also, these facilities provide tracking aid to radio-frequency telemetry stations with the help of which, the telemetry systems acquire the MUT for monitoring the telemetry health parameters including inertial navigation system (INS) data 1,2 . Thus, accurate testing of the missiles depends directly on the calibration of these tracking sensors so that the trajectories of the MUT generated by various tracking sensors do not provide erroneous or misleading results.…”
Section: Introductionmentioning
confidence: 99%